The construction of a low cost airline network - Kai Hüschelrath; Kathrin Müller; Volodymyr Bilotkach (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
The paper investigates the construction of a low cost airline network by analyzing JetBlue Airways' entry decisions into nonstop domestic U.S. airport-pair markets between 2000 and 2009. Adopting duration models with time-varying covariates, we find that JetBlue consistently avoided concentrated airports and targeted concentrated routes; network economies also affected entry positively. For non-stop entry into a route that has not been served on a non-stop basis before, our analysis reveals that the carrier focused on thicker routes and secondary airports, thereby avoiding direct confrontation with network carriers. Non-stop entry into existing non-stop markets, however, shows that JetBlue concentrated on longer-haul markets and avoided routes already operated by either other low cost carriers or network carriers under bankruptcy protection.
Keywords: L11; L23; L93; 330; Airline industry; network; entry; low cost carrier; Luftverkehrsgesellschaft; Niedrigpreisstrategie; Markteintritt; Network Externalities; USA